Tirofiban Blocks Platelet Adhesion to Fibrin with Minimal Perturbation of GpIIb/IIIa Structure - Hantgan, Roy R.; Stahle, Mary C.; Jerome, Gray W.; Nagaswami, Chandrasekaran; Weisel, John W. (Thrombosis and Haemostasis, 2002)
A biophysical approach tested the hypothesis that tirofiban, like eptifibatide, perturbs GpIIb/IIIa structure. Tirofiban bound tightly to platelet GpIIb/IIIa (EC50 ∼ 24 nmol/L) and effectively inhibited platelet aggregation (IC50 ∼ 37 nmol/L) but blocked platelet adhesion to clotted fibrin only at much higher doses (IC50 ∼ 580 nmol/L). Electrophoretic analyses demonstrated that tirofiban protected GpIIb/IIIa from SDSinduced subunit dissociation. However, saturating tirofiban concentrations had little or no effect on GpIIb/IIIa secondary or tertiary structure, as determined by circular dichroic spectroscopy, dynamic light scattering, and sedimentation velocity measurements performed with purified receptors in octyl glucoside. Moderate dose-dependent effects on GpIIb/IIIa quaternary structure were detected by sedimentation equilibrium. Transmission electron microscopy showed minimal tirofiban-induced receptor activation or oligomerization. Thus, even at the increased concentrations needed to block platelet:fibrin adhesive interactions, tirofiban exhibited only limited effects on GpIIb/IIIa conformation and clustering. Our results provide new insights into the mechanisms and potential prothrombotic complications of integrin antagonists.
Keywords: GpIIb/IIIa; integrin αIIbβ3; integrin antagonist; fibrin; structure